The Potential of Traditional Societies, and of Anthropology, Their Predator - Cruikshank, Julie (Anthropologica, 2022)
Anthropology is sometimes characterized as a discipline which studies the obsolete; that is, "primitive" isolated societies. This paper suggests that, in fact, the designs for living found in traditional cultures, particularly in the Canadian North, may have application to post-industrial society. It is possible that anthropologists may have a particular role in suggesting some of the lessons, embodied in traditional cultures, which could be useful to 'modern' western man. If so, this could provide alternatives to assumptions that thorough westernization inevitably and necessarily precedes modernization.